2016
DOI: 10.1016/j.jenvman.2016.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of a three-stage on-farm biobed in treating pesticide contaminated wastewater

Abstract: 11Agricultural point source pesticide pollution arising from contaminated machinery washings and 12 accidental spillages pose a significant threat to river water and groundwater quality. In this study, we 13 assess the effectiveness of a three-stage on-farm biobed for treating pesticide contaminated waste 14 water from a large (20 km

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The presence of annamox may be due to high concentrations of organic carbon in the STU resulting in concurrent denitrification with heterotrophic Denitrifiers (Chamchoi et al, 2008). These results match previous studies which suggested that anammox was active within low flow sites and at 5-7.5 cm depths within the infiltrative surface (Cooper et al, 2016;Humphrey Jr et al, 2019). Increases in functional richness may help locate metabolic activities such as the presence of denitrifiers at the proximal position to the inlet at the SE-STU (Louca et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…The presence of annamox may be due to high concentrations of organic carbon in the STU resulting in concurrent denitrification with heterotrophic Denitrifiers (Chamchoi et al, 2008). These results match previous studies which suggested that anammox was active within low flow sites and at 5-7.5 cm depths within the infiltrative surface (Cooper et al, 2016;Humphrey Jr et al, 2019). Increases in functional richness may help locate metabolic activities such as the presence of denitrifiers at the proximal position to the inlet at the SE-STU (Louca et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…In fact, most of the operators that were interviewed used aged atomizers, which do not require the technical features requested by Directive 2009/127/EC for new machinery. Also, different procedures to avoid point source contamination have been suggested depending on both the specific context, and the size and shape of the equipment used [62,[83][84][85][86][87][88]. Moreover, to the authors' knowledge a few companies have at their disposal a specific area for the cleaning of the application equipment, while in the considered sample none of the interviewed companies has this type of facility.…”
Section: Limitationsmentioning
confidence: 99%
“…This paper focuses on the intensive arable system of the River Wensum DTC, where monitoring of water quality and soil parameters commenced in April 2011 and now provides an invaluable record of baseline conditions before and after the implementation of mitigation measures since autumn 2013 (Cooper et al, 2018;Cooper et al, 2020). The measures implemented within the River Wensum DTC include a biobed to degrade waste pesticides (Cooper et al, 2016), constructed wetlands to capture sediment-rich road runoff (Cooper et al, 2019) and the extensive use of cover crops and conservation tillage practices to reduce nutrient leaching and improve soil health within a seven-year crop rotation (Cooper et al, 2017).…”
Section: Introductionmentioning
confidence: 99%